2019 IEEE International Symposium on Applications of Ferroelectrics (ISAF) 2019
DOI: 10.1109/isaf43169.2019.9034976
|View full text |Cite
|
Sign up to set email alerts
|

BiFeO3 synthesis by conventional solid-state reaction

Abstract: BiFeO3 is a multiferroic material with the perovskite structure which is promising for use in sensors and transducers. Single phase production of BiFeO3 remains a challenge, however. In this study, the optimal calcination temperature to obtain close to single phase powder was determined to be 750 °C. The sintering temperature of 775 °C was also found to obtain high density ceramics ( ≈ 95 % of theoretical density). It is shown that off-stoichiometry of bismuth oxide in precursors effects the content of seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…All binary and ternary ceramics produced in this work exhibit an average grain size of about 4-7 µm. An earlier study on BFO-PT ceramics reported a grain size of about 1 µm [1], while single-phase BFO sintered to a fully dense state could have a grain size of 10 µm [2]. The increase in the grain size in the ternary system with respect to the binary system might be due to a decrease in tetragonality upon the addition of ST.…”
Section: Microstructure and Crystal Structurementioning
confidence: 99%
See 2 more Smart Citations
“…All binary and ternary ceramics produced in this work exhibit an average grain size of about 4-7 µm. An earlier study on BFO-PT ceramics reported a grain size of about 1 µm [1], while single-phase BFO sintered to a fully dense state could have a grain size of 10 µm [2]. The increase in the grain size in the ternary system with respect to the binary system might be due to a decrease in tetragonality upon the addition of ST.…”
Section: Microstructure and Crystal Structurementioning
confidence: 99%
“…For example, conventional ultrasonic echography measurements of the wall thickness of pipes and tanks offer advantages over other non-destructive testing methods, such as low cost, ease of operation, and the ability to conduct in operando measurements [1]. Piezoelectric sensors are already well established for this type of application but are limited to operating temperatures of up to 260 • C [2] due to most devices relying on the ubiquitous piezoelectric ceramic lead zirconate titanate or PZT. Therefore, considerable efforts are now aimed at developing materials that can satisfy the growing demand for piezoelectric elements with operating temperatures within the range of 350-600 • C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the covalency and ionicity of alkaline metals lithium (Li), Na, and K (designated as MA) were investigated based on For piezoelectric perovskites, alkaline and alkaline-earth metals are traditionally regarded as representative ionic species occupying the site of Pb or A [17]. Although there are more modern systems such as BNT [10][11][12][13] and BNT-based solid solutions [18], we focused on traditional systems, namely, BiFeO 3 [19] and GaFeO 3 [20], since our work was on the efficient use of ubiquitous alkaline and alkaline-earth metals. Both species of traditional systems are ionic; their formal ionic charges are 1+ and 2+, respectively.…”
Section: Calculationmentioning
confidence: 99%
“…Among multiferroic materials, perovskite BiFeO 3 (BFO) is one of the few and best known room-temperature multiferroics, that has a distorted perovskite structure that belongs to rhombohedral R3c symmetry (with a = 3.958 and α = 89.30 • ), with a high ferroelectric Curie temperature (T C = 830 • C) and antiferromagnetic order (T N = 370 • C) [11][12][13]. The preparations of BiFeO 3 powder material were reported by different synthesis methods, as for example: solid-state reaction method [14], hydrothermal synthesis route [15], sol-gel process [16] combustion method [17], Pechini method [18], and microwave synthesis [19]. However, the preparation of BiFeO 3 is very difficult due to: (i) The kinetics of phase formation in the Bi 2 O 3 -Fe 2 O 3 system that leads to the formation of impurities along with the perovskite major phase [20] and thermal stability; (ii) valence fluctuation of iron (Fe 3+ /Fe 2+ transitions) which leads to the variation of oxygen stoichiometry and appearance of the oxygen vacancies as defects; (iii) Bi volatilization because bismuth oxide has a low melting point.…”
Section: Introductionmentioning
confidence: 99%